Microemulsions containing centella asiatica extract as antioxidant and anti-acetylcholinesterase agent - Ghazali, Muhammad Ihsan (2019)
The treatment of Alzheimer's disease (AD) has gained much attention due to the current and predicted prevalence of the disease. Centella asiatica hydroalcoholic extract (CAHE), lemongrass essential oil (LGEO) and virgin coconut oil (VCO) presenting antioxidant and acetylcholinesterase inhibition activity derived from natural products to enhanced memory of AD patients. In the present study, the ternary phase behaviour diagrams were constructed based on microemulsion (ME) containing CAHE with varying ratios of LGEO or VCO, and non-ionic surfactant, Tween 20 (T20) or Tween 80 (T80). The formulated MEs were characterized for the identification of functional groups by fourier transform infrared (FTIR), thermal behaviour by differential scanning colorimetry (DSC), and morphology and particle size by atomic force microscopy (AFM). The ME formulations were also tested for antioxidant activity by DPPH, ABTS, and FRAP assays, anti-acetylcholinesterase activity, in-vitro drug release, and cytotoxicity assay. Four ternary phase diagrams were successfully constructed and based on each ternary diagram, four transparent MEs were selected. The results of this study show that the particles of MEs were spherical in shape with an average particle size range of 0.1 – 0.2 μm. Thermodynamic and long-term storage stability tests conducted at room temperature showed that all the ME formulations had good stability without any phase separation. All the ME formulations revealed good antioxidant and anti-AChE activities. F1 (Tween 20/LGEO:CAHE) showed the highest antioxidant activities of DPPH, ABTS and FRAP is 79.3 %, 93 %, and 1.234 mmol Fe2+ E/L, respectively, and for anti-AChE activity is 43.23%. Moreover, 60% of F1 was released within 24 h across the semi-permeable membrane dialysis bag. Additionally, the brine shrimp lethality assay (BSLA) showed a mortality 10%. In conclusion, this study shows that F1 has good antioxidant and anti-acetylcholinesterase activities which can play a promising role as potential antioxidant and anti-AChE therapeutic agent.